Comparison of Iran National and Provincial Economic Structure Using the Input-Output Approach - Hossein Aliasgharpour Moziraji; Nooraddin Sharify (پژوهشهای اقتصادی, 2020)
One of the basic functions of input-output analysis is to identify the economic structure of regions and countries. This research seeks to identify the key sectors of Iran's provinces and to compare them with national key sectors. The data is extracted from the national input-output table and regional accounts of the Statistical Center of Iran in 2011. The results show that based on the "total gross backward and forward linkages" criterion, there are 17 and 20 key sectors, respectively, with and without considering the "dispersion of the linkages", at national level. With same criterion, every province has at least one and two key sectors, respectively. However, some key sectors of provinces are not listed as national key sectors, and are not included in the central planning. On the contrary, a number of national key sectors are not categorized as key sectors in the provincial level. In addition, due to the larger usage of national resources in key sectors, the provinces with more common key sectors with national economy have higher GDP per capita. Thus, it seems due to inconsistency between some regional economic structure with national one, considering the provincial key sectors in national economic planning leads to optimal use of national resources through increasing the GDP per capita and decreasing the interregional disparities.